Estimation of axial stiffness on existing and reinforcing piles in vertical extension remodeled buildings. (15th November 2019) - Kim, Dohyun; Kim, Jaehong; Jeong, Sangseom
Highlights: Load distribution ratio of piles before and after the vertical extension are investigated. Changes of load distribution ratio of existing and reinforcing piles are clarified. Various factors for optimal design of reinforcing piles are rigorously studied. Methodology in estimating the axial stiffness reinforcing piles are proposed. Abstract: In this study, the load distribution ratio (LDR) and axial stiffness of reinforcing piles in vertical extension remodeling structure will be investigated through numerical calculation and case studies. By comparing the results between existing and reinforcing piles, the efficiency of the reinforcing piles will be observed. To further understand the LDR of piles, the effect of elastic modulus of raft, pile end-bearing condition, raft rigidity, and the relative position of reinforcing pile in a group were investigated by using 3D FE analysis. The numerical model was validated based on actual field measurements. In addition, the method in estimating the axial stiffness of reinforcing piles ( Kvr ) was presented which is based on (1) the axial stiffness of existing piles ( Kve ) by using the 3D computer-based method, YSPR (Yonsei Piled Raft), and (2) by reducing the axial stiffness of existing piles by considering the aging and the deterioration process. The results of this can justify the necessity for settlement-based design and improvement of piled-raft foundation of vertical extension remodeling. The conclusions in this paper will significantly contribute to ensuring the safety and integrity of the structure during vertical extension remodeling process and throughout the service period.